The Addition of Telang Flower (Clitoria ternatea) in Tempeh with Different Fermentation Time - Anisa Rahmawati; Adnan Putra Pratama; Andi Lisnawati; Farida Aryani; Anis Syauqi (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2024)
Tempeh is an important part of Indonesia's culinary culture. Tempeh is a food that contains a high source of vegetable protein. So far, the tempeh on the market is tempeh without any mixture of ingredients. The addition of telang flowers which have been beneficial for health is one of the innovations because telang flowers contain anthocyanins, flavonoids, phenolic acids which have an effect on the human body so that it is hoped that this research will be able to produce innovations and added value from telang flowers. One of them is the innovation of telang flower tempeh products. The purpose of this study was to examine the characteristics of making tempeh with the addition of natural coloring from telang flowers with different fermentation times based on the test of water content, ash content, and the level of panelist preference based on the hedonic test, for tempeh formulations with a combination of telang flowers. This research was conducted with the method of Completely Randomized Design (CRD) with 1 treatment factor, namely different fermentation times (P1) 24 hours (P2) 48 hours and (P3) 72 hours with repetition of parameters testing water content, ash content, hedonic test. The results showed that in making tempeh with the addition of telang flowers, the highest water content was P2 treatment (61.54%) and there was the lowest value of P1 (60.51%). The results of the highest tempeh ash content are treatment (P1) 2.7%, the lowest value is (P3) 1.11%. In the hedonic test of telang flower tempeh, the color test had the highest value (P3) 3.43 (like) the lowest value (P2) 3.27 (like).In the texture hedonic test there was the highest value (P2) 3.40 (like) the lowest value (P1) 3.13 (like) And in the aroma hedonic test there was the highest value (P3) 3.25 (like) the lowest value (P1) 3.08 (like).